Red Hot Chili Pepper. A New Calluella Stoliczka, 1872 (Lissamphibia: Anura: Microhylidae) from Sarawak, East Malaysia (Borneo) - Das, Indraneil; Min, Pui Yong; Hsu, Wayne W.; Hertwig, Stefan T.; Haas, Alexander (Zootaxa, 2014)
A new brightly-coloured (olive and red) species of microhylid frog of the genus Calluella Stoliczka 1872 is described from the upper elevations of Gunung Penrissen and the Matang Range, Sarawak, East Malaysia (Borneo). Calluella capsa, new species, is diagnosable in showing the following combination of characters: SVL up to 36.0 mm; dorsum weakly granular; a faint dermal fold across forehead; toe tips obtuse; webbing on toes basal; lateral fringes on toes present; outer metatarsal tubercle present; and dorsum greyish-olive, with red spots; half of venter bright red, the rest with large white and dark areas. The new species is the eighth species of Calluella to be described, and the fourth known from Borneo. A preliminary phylogeny of Calluella and its relatives is presented, and the new taxon compared with congeners from Malaysia and other parts of south-east Asia.